2020
DOI: 10.1007/s12012-020-09566-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Electrocardiographic Repolarization Parameters During Antiandrogen Therapy in Patients with Prostate Cancer and Hypogonadism

Abstract: We assessed the effects of antiandrogen therapy on ECG parameters of ventricular repolarization related to arrhythmic risk in 35 patients aged 70.3 ± 7 years with advanced prostate cancer treated with degarelix associated with enzalutamide (group A, 26 patients) or degarelix monotherapy (group B, 9 patients). We analyzed Fridericia corrected Q-T interval (QTc), Q-T dispersion (QTd), J-Tpeak interval (JTp), mean and maximum Tpeak-Tend interval (Tpe) and Tpe/QT ratio, Tpeak-Tend dispersion (Tped), index of cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…This is the first study to assess the influence of testosterone on drug‐induced lengthening of J‐T peak and T peak ‐T end . However, Gheorge et al 23 . reported that 6 months of antiandrogen therapy was associated with significant increases in QT interval, maximum T peak ‐T end , mean T peak ‐T end /QT, and T peak ‐T end dispersion in patients with prostate cancer and hypogonadism.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to assess the influence of testosterone on drug‐induced lengthening of J‐T peak and T peak ‐T end . However, Gheorge et al 23 . reported that 6 months of antiandrogen therapy was associated with significant increases in QT interval, maximum T peak ‐T end , mean T peak ‐T end /QT, and T peak ‐T end dispersion in patients with prostate cancer and hypogonadism.…”
Section: Discussionmentioning
confidence: 99%
“…The adipose tissue accumulates mainly subcutaneously without changes in waist-hip ratio. ADT can also induce fatal ventricular arrhythmia by lengthening Q-T interval on ECG [ 38 , 39 , 40 ] due to hypogonadism but also by a direct effect on I k currents in myocardial cells, described experimentally for some ADT [ 38 ] ( Figure 3 ). ADT raises the thrombotic risk by increasing the serum level of fibrinogen, as demonstrated by Ziaran et al [ 41 ] in 97 patients with locally advanced prostate cancer after 12 months of treatment, but not the serum level of CRP [ 16 , 42 ].…”
Section: Cardiovascular Effects Of Adtmentioning
confidence: 99%
“…In a recent study [ 39 ] which included 35 patients with advanced prostate cancer and secondary hypogonadism induced by 6 months ADT, there was a significant alteration of ECG parameters associated with arrhythmic risk: prolongations of QT interval corrected to the cardiac rate, QT dispersion, maximal value of Tpeak-Tend interval, mean ratio Tpe/QT and maximal ratio Tpe/QT, Tped. In patients which undergone an echocardiographic study there was also a subclinical alteration of global longitudinal strain and mechanical dispersion evaluated by echocardiography [ 67 ].…”
Section: Cardiovascular Effects Of Adtmentioning
confidence: 99%
“…Acquired male hypogonadism in patients receiving ADT for prostate cancer therapy has been reported as a risk factor for acquired LQTS and TdP [ 17 , 85 , 90 , 91 , 92 ] and normalization of the testosterone level by HRT attenuates the modification of QTc duration in hypogonadal males [ 85 , 93 , 94 ]. In a case series of seven consecutive men prospectively admitted for TdP, we showed that all had acquired hypogonadism and that normalization of testosterone levels shortened QTc and prevented recurrence of TdP [ 17 ].…”
Section: Exogenous Hormonal Therapy and Its Effect On Qtc Variatiomentioning
confidence: 99%